2022
DOI: 10.1177/02557614221087340
|View full text |Cite
|
Sign up to set email alerts
|

Music professionalism promoting gerotranscendence: An instrumental case study of healthcare musicians in an eldercare hospital

Abstract: The effect of ever-increasing life expectancy on global demographics has had a significant impact on many professional landscapes, not only in social services and healthcare but more broadly. This instrumental case study explores professional healthcare musicians’ work through their collaborative, socially engaged music-making practice in eldercare hospital wards. Two healthcare musicians were interviewed, and their work and professional practices were observed in the infection and orthopedic wards of an arts-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…We consider it a priority to develop a curriculum able to offer students interested in this type of work sufficient preparation to act independently as music facilitators for the older population. This idea is also supported by recent studies that emphasize the need to find effective ways to promote the health and wellbeing of residents in nursing homes by facilitating the engagement with music (Garrido et al, 2020;Koivisto and Laes, 2022). This implies a high level in a wide range of musical skills, so that they can sing, drum, arrange, and conduct.…”
Section: Avenues For Further Researchmentioning
confidence: 88%
See 1 more Smart Citation
“…We consider it a priority to develop a curriculum able to offer students interested in this type of work sufficient preparation to act independently as music facilitators for the older population. This idea is also supported by recent studies that emphasize the need to find effective ways to promote the health and wellbeing of residents in nursing homes by facilitating the engagement with music (Garrido et al, 2020;Koivisto and Laes, 2022). This implies a high level in a wide range of musical skills, so that they can sing, drum, arrange, and conduct.…”
Section: Avenues For Further Researchmentioning
confidence: 88%
“…Implementing this type of training steadily and beyond the geographical area where A4A was carried out could offer significant benefits to students, music universities and local communities, promoting the development of "innovative ways of supporting the holistic wellbeing of all participants, integrating the whole professional community into the ongoing creation of novel musical spaces" (Koivisto and Laes, 2022). As for students, involvement in community-based programs can foster transformative learning (Perkins et al, 2015) and meaningful learning experiences in terms of musical and extra-musical skills (Renshaw, 2010;Smilde, 2018), with positive effects on employability, identity, and health and wellbeing (Triantafyllaki and Anagnostopoulou, 2013;Smilde et al, 2019;Paolantonio et al, 2022).…”
Section: Avenues For Further Researchmentioning
confidence: 99%
“…While the research reported in this article involved the participation of a small group of conservatoire-trained classical musicians working in one specific context, the findings could be translated to musicians working in other professional contexts such as music educators, facilitators, and community practitioners. The need for them to be versatile, empathetic, and make connections has been shown in research worldwide involving musicians in pediatric hospitals (Tomlinson & Habron, 2021), music practitioners in healthcare settings in Italy (Preti & Welch, 2013), and eldercare hospitals in Finland (Koivisto & Laes, 2022).…”
Section: Implications For Practicementioning
confidence: 99%
“…How to rapidly promote the effective transformation of music teaching mode in colleges and universities in the era of new media has also become the current educational task. Literally, music and education are two parts of music education [1] . In music education, teachers combine the two elements to form a whole through certain methods, which is the word "teaching".…”
Section: Introductionmentioning
confidence: 99%